2013
DOI: 10.1246/cl.130710
|View full text |Cite
|
Sign up to set email alerts
|

Density Function Theoretical Investigation on the Ni3PP Structure and the Hydrogen Adsorption Property of the Ni2P(0001) Surface

Abstract: Electronic and structural properties of phosphorus terminated structure of Ni 2 P(0001) surface(Ni 3 PP) are investigated by density functional theoretical (DFT) calculation. Phosphorus adsorption largely stabilizes the Ni 2 P(0001) surface by creating Ni-P bonds on the Ni trimer. Atomic hydrogen can adsorb on the topmost P site but its adsorption energy is much lower than its adsorption energy on the Ni trimer site of Ni 3 P 2 surface. Our results suggest that the Ni trimer is the key factor for high catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…In addition, since the P 2 atoms possess a slight negative charge (-0.07e), they provide additional sites for 3 hydrogen adsorption [15,36]. This theoretical proposal has also been supported by 4 studies of the electronic structure of Ni2P [35].…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…In addition, since the P 2 atoms possess a slight negative charge (-0.07e), they provide additional sites for 3 hydrogen adsorption [15,36]. This theoretical proposal has also been supported by 4 studies of the electronic structure of Ni2P [35].…”
mentioning
confidence: 73%
“…Many efforts have been made to date to elucidate the surface properties of Ni2P 10 single crystal surfaces, using X-ray photoelectron spectroscopy (XPS) [22,23], scanning 11 tunneling microscopy (STM) [24][25][26][27][28], low-energy electron diffraction (LEED) [24][25][26][27][28][29][30], 12 photoemission electron microscopy (PEEM) [25], photoelectron diffraction [31] and 13 photoemission spectroscopy (PES) [30,[32][33][34][35]. Theoretical calculations using density 14 functional theory (DFT) [11,14,15,[36][37][38] have also played an important role in 15 understanding the catalytic properties of the surface. These studies have indicated that 16 the Ni2P single crystal surface is stabilized by reordering of the P atoms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations